2020
DOI: 10.3982/ecta15362
|View full text |Cite
|
Sign up to set email alerts
|

On the Geography of Global Value Chains

Abstract: This paper develops a multi‐stage general‐equilibrium model of global value chains (GVCs) and studies the specialization of countries within GVCs in a world with barriers to international trade. With costly trade, the optimal location of production of a given stage in a GVC is not only a function of the marginal cost at which that stage can be produced in a given country, but is also shaped by the proximity of that location to the precedent and the subsequent desired locations of production. We show that, othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(105 citation statements)
references
References 70 publications
5
95
0
5
Order By: Relevance
“…Johnson and Noguera (2017) show that countries that expanded GVCs more were those with higher GDP growth in their sample of more than 40 countries over the period 1970-2007. In this paper, we build a dynamic two-country model featuring sequential, multi-stage production and capital accumulation to study the joint dynamics of investment, growth and GVC trade. Specifically, we introduce capital accumulation and growth into the GVC trade model of Antràs and de Gortari (2020). Consistent with the empirical findings, our model implies that declining trade costs expand GVC trade across countries, particularly in the faster growing economy.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…Johnson and Noguera (2017) show that countries that expanded GVCs more were those with higher GDP growth in their sample of more than 40 countries over the period 1970-2007. In this paper, we build a dynamic two-country model featuring sequential, multi-stage production and capital accumulation to study the joint dynamics of investment, growth and GVC trade. Specifically, we introduce capital accumulation and growth into the GVC trade model of Antràs and de Gortari (2020). Consistent with the empirical findings, our model implies that declining trade costs expand GVC trade across countries, particularly in the faster growing economy.…”
Section: Introductionsupporting
confidence: 55%
“…This is because trade costs apply to the gross value, and the later stages compound trade costs from all previous stages; hence, trade in earlier stages effectively incurs lower costs. This pattern is also pointed out by Antràs and de Gortari (2020). Owing to the symmetry, the presence of endogenous capital accumulation does not affect the dynamics of GVC trade, but GVC trade does impact the dynamics of investment and capital accumulation quantitatively and qualitatively.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Authors like Antràs and De Gortari (2017) have suggested that trade costs have a more detrimental effect on downstream than upstream production stages. As the alleged weakness of African exports is generally explained by the higher level of trade costs borne by these countries, it would not be surprising to find a lower penalty on their trade in intermediate goods than on their trade in final goods.…”
Section: Econometric Resultsmentioning
confidence: 99%